2020
DOI: 10.1093/nar/gkaa170
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced affinity of racemic phosphorothioate DNA with transcription factor SATB1 arising from diastereomer-specific hydrogen bonds and hydrophobic contacts

Abstract: Phosphorothioate modification is commonly introduced into therapeutic oligonucleotides, typically as a racemic mixture in which either of the two non-bridging phosphate oxygens is replaced by sulfur, which frequently increases affinities with proteins. Here, we used isothermal titration calorimetry and X-ray crystallography to investigate the thermodynamic and structural properties of the interaction between the primary DNA-binding domain (CUTr1) of transcription factor SATB1 and dodecamer DNAs with racemic ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…63 Favorable PSO-mediated protein−DNA and −RNA interactions compared to the parent all-PO2 species are commonly attributed to diastereoisomer-specific hydrophobic contacts. 64,65 However, in this study, the key contribution to the increased stability afforded by the Rp-PSO− and PS2−base face-on interaction stems primarily from enhanced dispersion attraction, as suggested by the calculations and dramatically supported by the thermodynamic measurements for the Rp-PSO stereoisomer that forms a face-centered complex with guanine. The observed similar stabilities of the PO2− and MePO−G interactions further support the conclusion that hydrophobics cannot be the main driver for the stability increases seen with thiophosphates.…”
Section: ■ Discussionmentioning
confidence: 59%
“…63 Favorable PSO-mediated protein−DNA and −RNA interactions compared to the parent all-PO2 species are commonly attributed to diastereoisomer-specific hydrophobic contacts. 64,65 However, in this study, the key contribution to the increased stability afforded by the Rp-PSO− and PS2−base face-on interaction stems primarily from enhanced dispersion attraction, as suggested by the calculations and dramatically supported by the thermodynamic measurements for the Rp-PSO stereoisomer that forms a face-centered complex with guanine. The observed similar stabilities of the PO2− and MePO−G interactions further support the conclusion that hydrophobics cannot be the main driver for the stability increases seen with thiophosphates.…”
Section: ■ Discussionmentioning
confidence: 59%
“…Particularly, as far as improving metabolic stability, pairing properties (RNA affinity), protein binding and transport/cellular uptake are concerned, chemical modifications are a prerequisite for the discovery and development of oligonucleotide therapeutics [11][12][13][14][15]. Thus, the natural PS and 2'-OMe backbone modifications provide improved resistance to degradation by exo-and endonucleases and they both affect protein binding [16,17]. Eight of the now approved 13 oligonucleotide drugs feature the PS modification in the backbone and all four approved siRNA therapeutics: ONPATTRO ® (patisiran, 2018), GIVLAARI ® (givosiran, 2019), OXLUMO ® (lumasiran, 2020) and LEQVIO ® (inclisiran, 2020) have 2'-OMe modifications [18][19][20][21] (https:// www.oligotherapeutics.org/20th-anniversary-of-rna-interference-in-mammalian-cells/).…”
Section: Introductionmentioning
confidence: 99%
“…Several high contact numbers are observed in outstanding inhibitions of the artificial phosphorothioate nucleotide complexes, e.g. , S2 sulfur in (poxvirus immune nuclease), 61 S1 and S2 in (transcription factor SATB1), 20 S2 in (DNA lyase), 62 (DNA polymerase I), 63 and (translation initiation factors), S1 in 64 (CRISPR-Cas Phi effector), and (hydrolase SAMHD1) 66 (see Table S6, ESI†). Many PS-nucleotide drug/inhibitor target proteins possess fewer than five contacts, such as in , 18 , 19 , 21 , 25 , , 65 , 67 , 68 , 69 70 and , 71 revealing that the sulfur atom accidentally (man-forcedly) replaces the “natural” phosphate non-bridging oxygen atom due to artificial reasons in drug development—it is opposite to virtually replace the natural sulfur atom of bacterial phosphorothioate DNA in the theoretical studies.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 The phosphorothioate (PS) and phosphorodithioate (PS2) investigations suggest that hydrophobic contacts between the PT-modified backbone and protein side chains enhance their affinities to the functional proteins (see Table S1, ESI †). 19,20 For instance, Seth et al reported a crystal structure for the human transcriptional cofactor PC4-DNA binding domain with a phosphorothioate 2 0 -OMe gap-mer antisense oligonucleotide, 21 in which the PS site has electrostatic and hydrophobic contacts with R70, R100, and K101. Similarly, Egli et al found that PS2 linkage increases the binding affinity of the MS2 coat protein binding with cognate RNA hairpin also by electrostatic and hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%